Propriedades mecânicas e correlação dos parâmetros de FSW e DS-FSW em alta velocidade na liga AA2050-T84, para a indústria aeronáutica - Ferreira, Felipe Santini (2018)
Friction Stir Welding (FSW) and DS-FSW (double pass FSW) processes were employed in the aluminum AA 2050 T-84 plate joints aiming to make possible to increase the welding speed above 5 mm / s, to obtain welds with optimized properties in relation to the base metal and to study the effects of the final microstructure. Microstructures of the welded joints were analyzed by optical microscopy and EBSD technique, to verify microstructure evolution and to find process defects formations. Mechanical properties were evaluated by microhardness and tensile tests, the results were used to find the conditions within the optimized welding parameters window. Fracture surfaces were analyzed by scanning electron microscopy. Thermal analyzes were measured by thermocouples to correlate the temperature peaks with the microstructural transformations. Fatigue tests were performed to verify the applicability in aeronautical structures. Finally, were performed welding by FSW with water cooling (WC-FSW) to reduce thermal cycle effects. The results obtained in this work showed satisfactory performance for FSW and DS-FSW, at high welding speeds were found to be suitable for the production of similar joints of the AA 2050-T84 alloy, with applications for the aeronautical industry. No significant difference was observed between the mechanical performance of FSW, DS-FSW and WC-FSW. The optimized condition for FSW (condition 3: 0,84 mm / s, 500 rpm, 7 mm/s) and DS-FSW (condition 2: 0,90 mm / rev, 400 rpm, 6 mm/s) resulted, respectively, yield limit, tensile strength limit and elongation of 62%, 77% and 44% and 67%, 77% and 38%, relative to that of the base material.